A new node-shifting method for shape optimization of reticulated spatial structures. (1st December 2017) - Ding, Chao; Seifi, Hamed; Dong, Shilin; Xie, Yi Min
Highlights: The new form-finding algorithm is applicable to general reticulated shells. The algorithm solves problems where the inverse hanging method would fail. Smooth surfaces can be obtained without an extra smoothing procedure. Abstract: The mechanical performance of a spatial structure is strongly influenced by the structural configuration. A generalized shape optimization algorithm is proposed to enhance the structure's stiffness in this paper. The nodal coordinates are treated as the design variables during the optimization process. At each iteration, based on the sensitivity analysis all the free nodes are moved along certain directions to reduce the compliance. A volume adjustment scheme is applied to satisfy the volume constraint. Jagged surfaces are automatically smoothed during the volume adjustment process and therefore no extra smoothing procedure is needed. A variety of 2D and 3D examples are presented to verify the effectiveness and the validity of the proposed method. It is shown that the new node-shifting method developed in this paper can be used for finding optimal shapes of general reticulated spatial structures including those with cantilevered parts where traditional inverse hanging method would fail.